Useful Reduction Mammoplasty Technique in Oncoplastic Breast Surgery and Reconstruction - Jong Ho Lee; Jeong Yeop Ryu; Kang Young Choi; Jung Dug Yang; Ho Yun Chung; Byung Chae Cho; Byeongju Kang; Jeeyeon Lee; Ho Yong Park; Joon Seok Lee (The Breast Journal)
Background. A combination of the reduction mammoplasty technique and breast reconstruction allows surgeons to lift ptotic breasts through local flaps and skin reduction during surgery for breast cancer. This study presents a reliable course for the combination of partial and skin or nipple-sparing mastectomy with reduction-reconstruction surgery. Methods. Fifty-seven patients underwent a partial mastectomy before reduction mammoplasty of both breasts during the same time period between 2014 and 2021 at our institution and thirteen patients underwent skin or nipple-sparing mastectomy, breast reconstruction with an extended latissimus dorsi flap or silicone implant, and aesthetic reduction mammoplasty of the contralateral breast during the same time period. Additional photos were obtained preoperatively, immediately after the operation, and at one, three, six, and twelve months postoperatively. Patient satisfaction was evaluated preoperatively and postoperatively and postoperative complications were noted. Results. Among the patients who underwent a partial mastectomy, the mean age was 45.18 ± 11.05 years, the mean body mass index (BMI) was 26.74 ± 3.53 kg/m2, and the mean preoperative right and left breast volumes were 663.85 (±28.12) cc and 664.34 (±37.13) cc, respectively, and the mean excised mass weight was 177.74 (±213.93) g. Among the patients who underwent a skin-sparing mastectomy, the mean age was 51.62 ± 8.96 years, the mean BMI was 26.91 ± 4.34 kg/m2, and the mean preoperative right and left breast volumes were 624.17 (±98.52) cc and 562.31 (±80.81) cc, respectively, and the mean excised mass weight was 618.05 (±338.17) g. Four patients (5.3%) in the partial mastectomy group had fat necrosis. The mean patient satisfaction score was higher postoperatively in both groups. Conclusion. Patients with breast cancer and large and/or ptotic breasts can successfully undergo reduction mammoplasty for both breasts immediately following partial mastectomy and nipple or skin-sparing mastectomy.